JAYA STAMBA MOTIF NGANJUK REGENCY FOR BESKAP AND JARIK CLOTHING ON MILLENNIAL KEBAYA - Aldi, Muhamad (Runtas : Journal Of Arts And Culture, 2023)
Creation of Final Project Work entitled Jaya Stamba Motif, Nganjuk Regency for Beskap and Jarik Clothing on Millennial kebaya. This final project aims to make beskap and kebaya dresses the newest models so that they are more attractive to the millennial generation by applying the Jaya Stamba motif, Nganjuk regency. The main source of ideas that form the basis for the creation of this work are various forms of Jaya Stamba motif ornaments and agricultural products of Nganjuk Regency. Jaya Stamba is an artifact originating from Nganjuk Regency, now it is a hallmark and was built in the middle of the city. The scope of the Jaya Stamba motif in Nganjuk Regency and agricultural products gave rise to the idea to be developed in the creation of batik. The creation process in making the work starts from observing the forms of Jaya Stamba and various things related to the natural wealth of Nganjuk Regency such as agricultural products and existing heritage sites. Observations through site surveys and print media were then carried out in the form of batik motifs and then poured into alternative patterns to be selected as batik motifs that would be applied to kebaya and beskap clothing. The results of the work amounted to 4, namely 2 beskap clothes and 2 kebaya clothes. Each is given a title according to the character and appearance and philosophy in it.